2013
DOI: 10.1289/ehp.1206068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Non-genetic Predictors of LINE-1 Methylation in Leukocyte DNA

Abstract: Background: Altered DNA methylation has been associated with various diseases.Objective: We evaluated the association between levels of methylation in leukocyte DNA at long interspersed nuclear element 1 (LINE-1) and genetic and non-genetic characteristics of 892 control participants from the Spanish Bladder Cancer/EPICURO study.Methods: We determined LINE-1 methylation levels by pyrosequencing. Individual data included demographics, smoking status, nutrient intake, toenail concentrations of 12 trace elements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 48 publications
2
70
1
Order By: Relevance
“…The main weakness is that the differences found are small. Recently, several studies 13,31 have evaluated the association between levels of LINE-1 methylation and different characteristics of healthy subjects in blood DNA. The significantly differences found were also within the range of values of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main weakness is that the differences found are small. Recently, several studies 13,31 have evaluated the association between levels of LINE-1 methylation and different characteristics of healthy subjects in blood DNA. The significantly differences found were also within the range of values of our study.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is well known that several of these environmental exposures are associated with risk of complex diseases, such as Type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted in the USA, China, and Spain to evaluate the association between exposure to lead and DNA methylation, generally discovering a trend towards hypomethylation. [235][236][237][238] In an epigenome-wide association study, 235 exposure to lead was negatively associated with methylation of a CpG site in the promoter of the COL1A2 gene. Exposure to lead in particulate matter is also related to the expression of microRNAs that are involved in oxidative stress and inflammation.…”
Section: Mechanistic Evidencementioning
confidence: 99%
“…Tajuddin et al [32] evaluated the association between LINE-1 methylation levels and genetic and non-genetic characteristics of 892 control participants form the Spanish Bladder Cancer/EPICURO study, and found that women had lower levels of LINE-1 methylation than men. van Bemme et al [19] also reported that buffy coat LINE-1 methylation levels differed by sex, with males having higher methylation than females in their study.…”
Section: Discussionmentioning
confidence: 99%